(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article explores the effects of implementing blockchain technology in supply chain management. Blockchain, as a decentralized and secure data accounting system, provides innovative opportunities to enhance transparency, traceability, and security in supply chain processes. The article examines the key advantages of blockchain usage, including improved transparency of all operations, reduced risks of fraud and errors, and reduced transaction processing costs and time. Special attention is given to how blockchain contributes to process optimization, business operation automation, and improved interaction among various supply chain participants. However, the adoption of this technology is not without challenges: technical issues, integration with existing systems, and the need for scaling solutions all require a careful approach. The potential of blockchain in various industries and its future in supply chain management are also discussed, along with possible new standards and solutions that may emerge as technologies adapt to changing market demands. The article highlights the importance of blockchain as a tool for achieving more efficient and secure supply chains, ensuring not only cost reduction but also improving overall resilience and reliability in supply chains in the context of globalization.